Effect of double rows plant system on plant growth, yield components and grain yield in prolific and non-prolific hybrid maize. Issue 1 (March 2020) - Alimuddin, S; Musa, Y; Azrai, M; Asrul, L
Abstract: Double row plant systems in corn plants theoretically can improve the efficiency of light interception in leaves, but their effect on grain yields is not consistent in each hybrid type. This research was conducted in the experimental garden of the Balai Penelitian Tanaman Serealia (Balitsereal) Maros Regency, South Sulawesi. This study aimed to evaluate the response of yields of prolific and nonprolific hybrid corn types to the double row and single row planting systems. Experimental design using Randomized Group Design in divided plot design that was carried out with three replications. The main plot was variety Nasa-29, Bisi-2 (prolific), Bima-19 (nonprolific), while subplot was a double row and single row. The double row planting system did not have a significant effect on plant height, number of leaves, and leaf area index (ILD), but a significant positive effect was found on the number of grains per row of ears, number of ears per plant, and percentage of the weight of the second ear's grains to the total yield and grain yield. In this study, the significant effect of double rows on each variety tested was not seen on all parameters tested. The double row planting system significantly increases the grain yield and the grain yield was consistent with the increase in the number of ear rows, the number of ear per plant and the percentage of grain weight of the second ears on yield, but not on plant height. The leaf area index achieved in this study may be one of the determinants of increased grain yield. A double row system can be considered as an alternative planting system, especially in the type of prolific hybrid corn to increase the contribution of two ears to grain yield.